Linear-elastic analysis of seismic responses of porcelain post electrical equipment. (15th December 2019) - Xie, Qiang; He, Chang; Jiang, Bin; Yang, Zhenyu
Highlights: A model was developed to obtain the seismic responses of electrical equipment. Linear-elastic joints were adopted in the model to simulate flanges. Supplemented braces were considered in the model. Abstract: A linear-elastic numerical model was developed to simulate electrical equipment mounted on a flexible support to evaluate its seismic performance. The electrical equipment and support were both simulated as beams, and flexible joints and braces were abstracted as linearly rotational and horizontal springs. The numerical model was validated by the results of shaking-table tests on a full-size 550-kV transformer bushing and a 220-kV transformer-bushing system. Parametric analyses were then performed on the electrical equipment–support system with flexible joints, rigid joints and braces. The results indicate that the model can simulate the dynamic properties and linear seismic responses of the electrical equipment–support system. The use of flexible joints would decrease the system's frequency. The flexible joints and braces also influence the system's seismic responses. Isolation effects can occur if the rotational stiffness of the flexible joint or bending stiffness of the supporting frame are small. To reduce the bending moment at the bottom cross section of the electrical equipment, the braces should have βEI and βEA values greater than 1 × 10 −10 . An installation angle of the braces between in the range of 40–70° is recommended to supplement to the system to reduce seismic responses.